Maternal Parenting in the Growth and Development of Children with Autism in Developed Countries: A Scoping Review - Nurbaity Nurbaity; Dewi Rokhanawati (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Autism Spectrum Disorder (ASD) is a developmental disorder that occurs in children.  Approximately 2.4 million children in Indonesia are diagnosed with autism. Comparing various parenting styles that affect the development and maturation of children with autism diagnoses in developed nations was the goal of this review. This review utilized the PRISMA-ScR checklist, PCC framework, and critical appraisal of articles by the Joanna Briggs Institute (JBI). Articles were collected from the PubMed, EBSCO, and Wiley databases and manual searches (Google Scholar and Research Rabbit) published from to 2013-2023. The search identified 123 articles and 18 duplicates. The screening results yielded 4 articles. The articles released in 2017 were one in, 2020 was two, and one in 2021. Each study used a cross-sectional design. The four selected articles were grouped by country of origin as follows: one from the United States, one from Japan, one from Brazil, and one from Indonesia. The examination of the four papers found that most mother parenting techniques with autistic children are democratic and impact the growth and development of autistic children in developed countries. Families may significantly enhance the care their autistic children receive and help them achieve the best developmental results by promoting evidence-based parenting techniques.